Successful management of Listeria spp. in an avocado processing facility. (April 2016) - Strydom, Amy; Vorster, René; Gouws, Pieter A.; Witthuhn, R. Corli
Abstract: Listeria monocytogenes can grow and multiply in various food matrices and cause severe human illness. Apart from the influence on consumer health, L. monocytogenes contamination of ready-to-eat (RTE) food products causes major economic losses due to product recalls. Control of foodborne pathogens in RTE food products is a challenge, specifically in foods that cannot undergo a heat-treatment during processing. The aim of this study was to develop control strategies for the management of L. monocytogenes in an avocado processing facility, additional to a quality control system. An in-house monitoring system (IMS) was established to test specifically for Listeria spp. in the final products and processing environment, including floors, equipment, work areas and personnel. Guacamole and environmental samples were collected and tested on-site for Listeria with the ISO 11290-1 method. Based on the prevalence of Listeria, the facility introduced new strategies in processing to counter cross contamination. Results from the 2014 guacamole production season showed almost complete eradication of Listeria spp. in final products (0.17%, n = 1170) and the processing facility (0.79%, n = 1520). This is a major achievement since the highest incidence of Listeria spp. over a period of five years was measured at 11.39% (n = 948) in the final product during the 2013 season and 13.44% (n = 1927) in the processing facility in 2011. These results indicate that successful management of Listeria spp. in an avocado processing facility can be accomplished with in-house monitoring of the listerial population and subsequent adjustments to the processing system. Highlights: We evaluated the Listeria contamination of an avocado processing facility. An in-house monitoring system was developed to monitor the Listeria . Cross contamination was the biggest concern in the facility. After 5 years the Listeria was almost eradicated from the facility.